Stres Kerja, Motivasi Kerja dan Kompensasi terhadap Kinerja Karyawan pada PT. Satria Mandiri - Muhamad Rizki Maulana; Sri Harini; Erni Yuningsih (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the effect of work stress (variable X1), work motivation (variable X2) and compensation (variable X3) on employee performance (Y). The method used in this research is descriptive and verification methods. The data collection techniques used by researchers in this research were observation, interviews, documentation and literature study. Data analysis techniques start from data preparation, data tabulation to the testing stage. Based on the results of multiple linear regression analysis research calculations. The coefficient of determination (R2) value can be obtained from the variables work stress (X1), work motivation (X2) and compensation (X3) which influence employee performance (Y) by 73.4%. The remaining 26.6% is influenced by other factors that Career development and work discipline were not included in this research. In conclusion, work stress, work motivation and compensation have an impact on employee performance. Keywords: Compensation, Employee Performance, Work Motivation, Job Stress